Effects of realistic groundplanes to NSA-measurements of open area test sites (OATS) - Battermann, Sven; Garbe, Heyno (2002 URSI General Assembly Proceedings)
The measurement of electromagnetic interference can be performed e.g. on open area test sites with different shapes and sizes, which are defined in ANSI C63.4 [1] and CISPR 16-1 [2]. For EMC compliance measurements the normalized site attenuation (NSA) has to be measured and compared with the calculated NSA [3]. If the deviation is too high, an extension of the groundplane is recommended. This paper shows, that not only the size but also the shape of the plane is very important to improve the correlation between a realistic and an ideal open area test site.